Housing starts in Canada, Japan, and the United States: Do forecasters herd? - Christian Pierdzioch; Jan Christoph Rülke; Georg Stadtmann (European University Viadrina, Department of Business Administration and Economics, 2012)
Recent price trends in housing markets may reflect herding of market participants. A natural question is whether such herding, to the extent that it occurred, reflects herding in forecasts of professional forecasters. Using survey data for Canada, Japan, and the United States, we did not find evidence of forecaster herding. On the contrary, forecasters anti-herd and, thereby, tend to intentionally scatter their forecasts around the consensus forecast. The extent of anti-herding seems to vary over time. For Canada and the United States, we found that more pronounced anti-herding leads to lower forecast accuracy.
Keywords: E37; D84; C33; 330; Housing starts; Forecasting; Herding